A comparison of methods for the registration of tractographic fibre images - Golding, Dan (Division of Biomedical Engineering, 2014)
Diffusion tensor imaging (DTI) and tractography have opened up new avenues in neuroscience and are allowing previously unexplored areas of neuroanatomy and function to be researched.